Unifying two views on multiple mean-payoff objectives in Markov decision processes - Chatterjee, Krishnendu; Křetínská, Zuzana; Kretinsky, Jan (Logical Methods in Computer Science)
We consider Markov decision processes (MDPs) with multiple limit-average (or mean-payoff) objectives. There exist two different views: (i) the expectation semantics, where the goal is to optimize the expected mean-payoff objective, and (ii) the satisfaction semantics, where the goal is to maximize the probability of runs such that the mean-payoff value stays above a given vector. We consider optimization with respect to both objectives at once, thus unifying the existing semantics. Precisely, the goal is to optimize the expectation while ensuring the satisfaction constraint. Our problem captures the notion of optimization with respect to strategies that are risk-averse (i.e., ensure certain probabilistic guarantee). Our main results are as follows: First, we present algorithms for the decision problems which are always polynomial in the size of the MDP. We also show that an approximation of the Pareto-curve can be computed in time polynomial in the size of the MDP, and the approximation factor, but exponential in the number of dimensions. Second, we present a complete characterization of the strategy complexity (in terms of memory bounds and randomization) required to solve our problem.

Nested weighted automata - Chatterjee, Krishnendu; Henzinger, Thomas A; Otop, Jan (ACM Transactions on Computational Logic (TOCL))
Recently there has been a significant effort to handle quantitative properties in formal verification and synthesis. While weighted automata over finite and infinite words provide a natural and flexible framework to express quantitative properties, perhaps surprisingly, some basic system properties such as average response time cannot be expressed using weighted automata or in any other known decidable formalism. In this work, we introduce nested weighted automata as a natural extension of weighted automata, which makes it possible to express important quantitative properties such as average response time. In nested weighted automata, a master automaton spins off and collects results from weighted slave automata, each of which computes a quantity along a finite portion of an infinite word. Nested weighted automata can be viewed as the quantitative analogue of monitor automata, which are used in runtime verification. We establish an almost-complete decidability picture for the basic decision problems about nested weighted automata and illustrate their applicability in several domains. In particular, nested weighted automata can be used to decide average response time properties.

Water wave packets - Jeschke, Stefan; Wojtan, Christopher J (ACM Transactions on Graphics)
This paper presents a method for simulating water surface waves as a displacement field on a 2D domain. Our method relies on Lagrangian particles that carry packets of water wave energy; each packet carries information about an entire group of wave trains, as opposed to only a single wave crest. Our approach is unconditionally stable and can simulate high resolution geometric details. This approach also presents a straightforward interface for artistic control, because it is essentially a particle system with intuitive parameters like wavelength and amplitude. Our implementation parallelizes well and runs in real time for moderately challenging scenarios.

Faster statistical model checking for unbounded temporal properties - Daca, Przemyslaw; Henzinger, Thomas A; Kretinsky, Jan; Petrov, Tatjana (ACM Transactions on Computational Logic)
We present a new algorithm for the statistical model checking of Markov chains with respect to unbounded temporal properties, including full linear temporal logic. The main idea is that we monitor each simulation run on the fly, in order to detect quickly if a bottom strongly connected component is entered with high probability, in which case the simulation run can be terminated early. As a result, our simulation runs are often much shorter than required by termination bounds that are computed a priori for a desired level of confidence on a large state space. In comparison to previous algorithms for statistical model checking our method is not only faster in many cases but also requires less information about the system, namely, only the minimum transition probability that occurs in the Markov chain. In addition, our method can be generalised to unbounded quantitative properties such as mean-payoff bounds.

Wild-type monomeric α-synuclein can impair vesicle endocytosis and synaptic fidelity via tubulin polymerization at the calyx of held - Eguchi, Kohgaku; Taoufiq, Zachari; Thorn Seshold, Oliver; Trauner, Dirk; Hasegawa, Masato; Takahashi, Tomoyuki (European Journal of Neuroscience)
α-Synuclein is a presynaptic protein the function of which has yet to be identified, but its neuronal content increases in patients of synucleinopa-thies including Parkinson’s disease. Chronic overexpression of α-synuclein reportedly expresses various phenotypes of synaptic dysfunction, but the primary target of its toxicity has not been determined. To investigate this, we acutely loaded human recombinant α-synuclein or its pathological mutants in their monomeric forms into the calyces of Held presynaptic terminals in slices from auditorily mature and immature rats of either sex. Membrane capacitance measurements revealed significant and specific inhibitory effects of WT monomeric α-synuclein on vesicle endocytosis throughout development. However, the α-synuclein A53T mutant affected vesicle endocytosis only at immature calyces, where as the A30P mutant had no effect throughout. The endocytic impairment by WTα-synuclein was rescued by intraterminal coloading of the microtubule (MT) polymerization blocker nocodazole. Furthermore, it was reversibly rescued by presynaptically loaded photostatin-1, a pho-toswitcheable inhibitor of MT polymerization, inalight-wavelength-dependent manner. Incontrast, endocyticinhibition by the A53T mutant at immature calyces was not rescued by nocodazole. Functionally, presynaptically loaded WT α-synuclein had no effect on basal synaptic transmission evoked at a low frequency, but significantly attenuated exocytosis and impaired the fidelity of neurotransmission during prolonged high-frequency stimulation. We conclude that monomeric WTα-synuclein primarily inhibits vesicle endocytosis via MT overassembly, thereby impairing high-frequency neurotransmission.

Planar matchings for weighted straight skeletons - Biedl, Therese; Huber, Stefan; Palfrader, Peter (International Journal of Computational Geometry and Applications)
We introduce planar matchings on directed pseudo-line arrangements, which yield a planar set of pseudo-line segments such that only matching-partners are adjacent. By translating the planar matching problem into a corresponding stable roommates problem we show that such matchings always exist. Using our new framework, we establish, for the first time, a complete, rigorous definition of weighted straight skeletons, which are based on a so-called wavefront propagation process. We present a generalized and unified approach to treat structural changes in the wavefront that focuses on the restoration of weak planarity by finding planar matchings.

Universality for a class of random band matrices - Bourgade, Paul; Erdös, László; Yau, Horng; Yin, Jun (Advances in Theoretical and Mathematical Physics)
We prove the universality for the eigenvalue gap statistics in the bulk of the spectrum for band matrices, in the regime where the band width is comparable with the dimension of the matrix, W ~ N. All previous results concerning universality of non-Gaussian random matrices are for mean-field models. By relying on a new mean-field reduction technique, we deduce universality from quantum unique ergodicity for band matrices.

Bogoliubov correction to the mean-field dynamics of interacting bosons - Nam, Phan; Napiórkowski, Marcin M (Advances in Theoretical and Mathematical Physics)
We consider the dynamics of a large quantum system of N identical bosons in 3D interacting via a two-body potential of the form N3β-1w(Nβ(x - y)). For fixed 0 = β < 1/3 and large N, we obtain a norm approximation to the many-body evolution in the Nparticle Hilbert space. The leading order behaviour of the dynamics is determined by Hartree theory while the second order is given by Bogoliubov theory.

Single sideband microwave to optical photon conversion-an-electro-optic-realization - Rueda Sanchez, Alfredo R; Sedlmeir, Florian; Collodo, Michele; Vogl, Ulrich; Stiller, Birgit; Schunk, Gerhard; Strekalov, Dmitry; Marquardt, Christoph; Fink, Johannes M; Painter, Oskar; Leuchs, Gerd; Schwefel, Harald (Optics InfoBase Conference Papers)
We present results on nonlinear electro-optical conversion of microwave radiation into the optical telecommunication band with more than 0.1% photon number conversion efficiency with MHz bandwidth, in a crystalline whispering gallery mode resonator

Scattering-aware texture reproduction for 3D printing - Elek, Oskar; Sumin, Denis; Zhang, Ran; Weyrich, Tim; Myszkowski, Karol; Bickel, Bernd; Wilkie, Alexander; Krivanek, Jaroslav (ACM Transactions on Graphics)
Color texture reproduction in 3D printing commonly ignores volumetric light transport (cross-talk) between surface points on a 3D print. Such light diffusion leads to significant blur of details and color bleeding, and is particularly severe for highly translucent resin-based print materials. Given their widely varying scattering properties, this cross-talk between surface points strongly depends on the internal structure of the volume surrounding each surface point. Existing scattering-aware methods use simplified models for light diffusion, and often accept the visual blur as an immutable property of the print medium. In contrast, our work counteracts heterogeneous scattering to obtain the impression of a crisp albedo texture on top of the 3D print, by optimizing for a fully volumetric material distribution that preserves the target appearance. Our method employs an efficient numerical optimizer on top of a general Monte-Carlo simulation of heterogeneous scattering, supported by a practical calibration procedure to obtain scattering parameters from a given set of printer materials. Despite the inherent translucency of the medium, we reproduce detailed surface textures on 3D prints. We evaluate our system using a commercial, five-tone 3D print process and compare against the printer’s native color texturing mode, demonstrating that our method preserves high-frequency features well without having to compromise on color gamut.

Towards unlicensed cellular networks in TV white spaces - Baig, Ghufran; Radunovic, Bozidar; Alistarh, Dan-Adrian; Balkwill, Matthew; Karagiannis, Thomas; Qiu, Lili (Proceedings of the 2017 13th International Conference on emerging Networking EXperiments and Technologies)
In this paper we study network architecture for unlicensed cellular networking for outdoor coverage in TV white spaces. The main technology proposed for TV white spaces is 802.11af, a Wi-Fi variant adapted for TV frequencies. However, 802.11af is originally designed for improved indoor propagation. We show that long links, typical for outdoor use, exacerbate known Wi-Fi issues, such as hidden and exposed terminal, and significantly reduce its efficiency. Instead, we propose CellFi, an alternative architecture based on LTE. LTE is designed for long-range coverage and throughput efficiency, but it is also designed to operate in tightly controlled and centrally managed networks. CellFi overcomes these problems by designing an LTE-compatible spectrum database component, mandatory for TV white space networking, and introducing an interference management component for distributed coordination. CellFi interference management is compatible with existing LTE mechanisms, requires no explicit communication between base stations, and is more efficient than CSMA for long links. We evaluate our design through extensive real world evaluation on of-the-shelf LTE equipment and simulations. We show that, compared to 802.11af, it increases coverage by 40% and reduces median flow completion times by 2.3x.

Amplification on undirected population structures: Comets beat stars - Pavlogiannis, Andreas; Tkadlec, Josef; Chatterjee, Krishnendu; Nowak, Martin (Scientific Reports)
The fixation probability is the probability that a new mutant introduced in a homogeneous population eventually takes over the entire population. The fixation probability is a fundamental quantity of natural selection, and known to depend on the population structure. Amplifiers of natural selection are population structures which increase the fixation probability of advantageous mutants, as compared to the baseline case of well-mixed populations. In this work we focus on symmetric population structures represented as undirected graphs. In the regime of undirected graphs, the strongest amplifier known has been the Star graph, and the existence of undirected graphs with stronger amplification properties has remained open for over a decade. In this work we present the Comet and Comet-swarm families of undirected graphs. We show that for a range of fitness values of the mutants, the Comet and Cometswarm graphs have fixation probability strictly larger than the fixation probability of the Star graph, for fixed population size and at the limit of large populations, respectively.

Couette-Poiseuille flow experiment with zero mean advection velocity: Subcritical transition to turbulence - Klotz, Lukasz; Lemoult, Grégoire M; Frontczak, Idalia; Tuckerman, Laurette; Wesfreid, José (Physical Review Fluids)
We present an experimental setup that creates a shear flow with zero mean advection velocity achieved by counterbalancing the nonzero streamwise pressure gradient by moving boundaries, which generates plane Couette-Poiseuille flow. We obtain experimental results in the transitional regime for this flow. Using flow visualization, we characterize the subcritical transition to turbulence in Couette-Poiseuille flow and show the existence of turbulent spots generated by a permanent perturbation. Due to the zero mean advection velocity of the base profile, these turbulent structures are nearly stationary. We distinguish two regions of the turbulent spot: the active turbulent core, which is characterized by waviness of the streaks similar to traveling waves, and the surrounding region, which includes in addition the weak undisturbed streaks and oblique waves at the laminar-turbulent interface. We also study the dependence of the size of these two regions on Reynolds number. Finally, we show that the traveling waves move in the downstream (Poiseuille) direction.

Activity dependent feedback inhibition may maintain head direction signals in mouse presubiculum - Simonnet, Jean; Nassar, Mérie; Stella, Federico; Cohen, Ivan; Mathon, Bertrand; Boccara, Charlotte; Miles, Richard; Fricker, Desdemona (Nature Communications)
Orientation in space is represented in specialized brain circuits. Persistent head direction signals are transmitted from anterior thalamus to the presubiculum, but the identity of the presubicular target neurons, their connectivity and function in local microcircuits are unknown. Here, we examine how thalamic afferents recruit presubicular principal neurons and Martinotti interneurons, and the ensuing synaptic interactions between these cells. Pyramidal neuron activation of Martinotti cells in superficial layers is strongly facilitating such that high-frequency head directional stimulation efficiently unmutes synaptic excitation. Martinotti-cell feedback plays a dual role: precisely timed spikes may not inhibit the firing of in-tune head direction cells, while exerting lateral inhibition. Autonomous attractor dynamics emerge from a modelled network implementing wiring motifs and timing sensitive synaptic interactions in the pyramidal - Martinotti-cell feedback loop. This inhibitory microcircuit is therefore tuned to refine and maintain head direction information in the presubiculum.

Clarifying the supercomplex: The higher-order organization of the mitochondrial electron transport chain - Letts, James A; Sazanov, Leonid A (Nature Structural and Molecular Biology)
The oxidative phosphorylation electron transport chain (OXPHOS-ETC) of the inner mitochondrial membrane is composed of five large protein complexes, named CI-CV. These complexes convert energy from the food we eat into ATP, a small molecule used to power a multitude of essential reactions throughout the cell. OXPHOS-ETC complexes are organized into supercomplexes (SCs) of defined stoichiometry: CI forms a supercomplex with CIII2 and CIV (SC I+III2+IV, known as the respirasome), as well as with CIII2 alone (SC I+III2). CIII2 forms a supercomplex with CIV (SC III2+IV) and CV forms dimers (CV2). Recent cryo-EM studies have revealed the structures of SC I+III2+IV and SC I+III2. Furthermore, recent work has shed light on the assembly and function of the SCs. Here we review and compare these recent studies and discuss how they have advanced our understanding of mitochondrial electron transport.

Nonhierarchical flux regulation exposes the fitness burden associated with lactate production in Synechocystis sp. PCC6803 - Du, Wei; Angermayr, Andreas; Jongbloets, Joeri; Molenaar, Douwe; Bachmann, Herwig; Hellingwerf, Klaas; Branco Dos Santos, Filipe (ACS Synthetic Biology)
Cyanobacteria are mostly engineered to be sustainable cell-factories by genetic manipulations alone. Here, by modulating the concentration of allosteric effectors, we focus on increasing product formation without further burdening the cells with increased expression of enzymes. Resorting to a novel 96-well microplate cultivation system for cyanobacteria, and using lactate-producing strains of Synechocystis PCC6803 expressing different l-lactate dehydrogenases (LDH), we titrated the effect of 2,5-anhydro-mannitol supplementation. The latter acts in cells as a nonmetabolizable analogue of fructose 1,6-bisphosphate, a known allosteric regulator of one of the tested LDHs. In this strain (SAA023), we achieved over 2-fold increase of lactate productivity. Furthermore, we observed that as carbon is increasingly deviated during growth toward product formation, there is an increased fixation rate in the population of spontaneous mutants harboring an impaired production pathway. This is a challenge in the development of green cell factories, which may be countered by the incorporation in biotechnological processes of strategies such as the one pioneered here.

Higson compactification and dimension raising - Austin, Kyle; Virk, Ziga (Topology and its Applications)
Let X and Y be proper metric spaces. We show that a coarsely n-to-1 map f:X→Y induces an n-to-1 map of Higson coronas. This viewpoint turns out to be successful in showing that the classical dimension raising theorems hold in large scale; that is, if f:X→Y is a coarsely n-to-1 map between proper metric spaces X and Y then asdim(Y)≤asdim(X)+n−1. Furthermore we introduce coarsely open coarsely n-to-1 maps, which include the natural quotient maps via a finite group action, and prove that they preserve the asymptotic dimension.

Plant biology: Building barriers… in roots - Von Wangenheim, Daniel; Goh, Tatsuaki; Dietrich, Daniela; Bennett, Malcolm (Current Biology)
The Casparian strip is an important barrier regulating water and nutrient uptake into root tissues. New research reveals two peptide signals and their co-receptors play critical roles patterning and maintaining barrier integrity.

Effects of VPAC1 activation in nucleus ambiguus neurons - Gherghina, Florin; Tica, Andrei; Deliu, Elena; Abood, Mary; Brailoiu, G.; Brǎiloiu, Eugen (Brain Research)
The pituitary adenylyl cyclase-activating polypeptide (PACAP) and its G protein-coupled receptors, PAC1, VPAC1 and VPAC2 form a system involved in a variety of biological processes. Although some sympathetic stimulatory effects of this system have been reported, its central cardiovascular regulatory properties are poorly characterized. VPAC1 receptors are expressed in the nucleus ambiguus (nAmb), a key center controlling cardiac parasympathetic tone. In this study, we report that selective VPAC1 activation in rhodamine-labeled cardiac vagal preganglionic neurons of the rat nAmb produces inositol 1,4,5-trisphosphate receptor-mediated Ca2+ mobilization, membrane depolarization and activation of P/Q-type Ca2+ channels. In vivo, this pathway converges onto transient reduction in heart rate of conscious rats. Therefore we demonstrate a VPAC1-dependent mechanism in the central parasympathetic regulation of the heart rate, adding to the complexity of PACAP-mediated cardiovascular modulation.

Finding non-orientable surfaces in 3-Manifolds - Burton, Benjamin; De Mesmay, Arnaud N; Wagner, Uli (Discrete & Computational Geometry)
We investigate the complexity of finding an embedded non-orientable surface of Euler genus g in a triangulated 3-manifold. This problem occurs both as a natural question in low-dimensional topology, and as a first non-trivial instance of embeddability of complexes into 3-manifolds. We prove that the problem is NP-hard, thus adding to the relatively few hardness results that are currently known in 3-manifold topology. In addition, we show that the problem lies in NP when the Euler genus g is odd, and we give an explicit algorithm in this case.